Evaluation of Islamic Religious Education Learning School-Based Program - Helma Heryati; Maria Borifar; Deri Wanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Evaluation in education is intended to get a picture of success in the learning process or learning program, which will later be used for improvement programs. This paper aims to describe the evaluation of Islamic education learning based on school programs. The research method used is a type of library research. Data sources come from literature which consists of primary data sources and secondary data sources. The results of the study show that the evaluation of Islamic religious learning is carried out comprehensively, continuously and integrated with school programs.